APPLICATION OF THE ANALYTIC HIERARCHY PROCESS METHOD IN EVALUATING PUBLIC COMPLAINT HANDLING SERVICE SATISFACTIONTHROUGH THE RAPID RESPONSE COMMUNITY (CRM) SYSTEM OF THE DKI JAKARTA PROVINCIAL GOVERNMENT - Andika Wisnuadji Putra Soebroto; Utomo Sarjono Putro (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Objectives: The study aims to analyze the factors that shape public satisfaction with the Cepat Respon Masyarakat (CRM) System. Methodology: Analytic Hierarchy Process (AHP) analysis with a mixed methods approach was used to compare paired cluster indicators identified by three CRM system experts. Finding: The results indicate that the level of public satisfaction with the CRM system, in the second-level cluster, is the most important factor determining public satisfaction, perceived quality. In the third-level cluster, the most important factors determining public satisfaction are Service Process Efficiency and Transparency. In the fourth-level cluster, the most important factors determining public satisfaction are the report and complaint development process, ease of procedures, and security of reporter data protection. Conclusion: The implementation of the CRM system must consider public opinion as users. Therefore, the DKI Jakarta Provincial Government needs to focus on improving transparency, accessibility, and operational management of public services to increase public trust.